The Fermented Cassava (Manihot esculenta C.) Flour and Bioimun as Additional Feed for the Juvenile Catfish (Clarias gariepinus) to Improve Growth, Immunity, and Survival - Asih, Supadmi; Hardi, Esti Handayani; Fitriyana, Fitriyana (Jurnal Perikanan Universitas Gadjah Mada, 2024)
The availability of fish feed has remained an obstacle in the fish cultivation until now. The dependence on fish flour, soy flour, the imported cornstarch has not been solved, though the natural resource in Indonesia supports the dependence of this raw material availability. This research was conducted by testing the use of the fermented cassava flour to substitute cornstarch as the catfish feed, by adding natural drug product, BIOIMUNÒ, which positively affected growth, immunity, and production. Research methodology used was the Completely Randomized Design with six treatments and three repetitions. Fishes with average weight of 10 g and length of 10 cm were raised in the aquarium with dimension of 60x40x40 cm, with the density of 10 fishes per aquarium. The research was conducted for 60 days with observation every 14 days. Compositions of cornstarch and cassava flour were P1 (0/200), P2 (100/100), P3 (75/125), P4 (50/150), P5 (25/175), and P6 (commercial feed), added with BIOIMUNÒ at 20 ml/kg from the extracts of Solanum ferox and Zingiber zerumbet. Feed was given three times at a percentage of 5%. This research showed the result that the best growth was in treatment (P3), with 75 g of cornstarch and 125 g of cassava flour (75/125). The highest absolute weight gain was in P3 at 132.67 ± 8.33 g. The immunity system testing was in accordance with the result of phytochemical test of positive alkaloid, negative flavonoid, and negative steroid. Survival Rate (SR) based on the variance analysis (ANOVA) had an insignificant effect (P>0.05) 93.00-100.00%. P3 feed conversion rate was 5.35±0.23. Hematocrit level and total erythrocyte with a decent score and total leukocyte increased from P6. Feed proximate test was in accordance with the standard. Total bacteria were in the normal range, the contamination test on heavy metal proved no harm against the catfishes, and the water quality was normal. In terms of economic analysis, P1-P5 were more affordable than (P6), so that it can be concluded that the fermented cassava flour can be used as a replacement of corn by adding BIOIMUNÒ as the catfish feed.